Harnessing the Power of Social Media in the Classroom: Challenging Students to Create Content to Share on Social Media Sites to Improve Learning Outcomes. Issue 3 (3rd July 2019) - Sohoni, Tracy
Abstract: Many young adults consume news, political, and historical information through social media sites, and yet students do not always connect this information to the academic knowledge they learn in their classes. In addition, while students learn academic writing and presentation skills, they may not feel equipped to present the knowledge that they have learned to a non-academic audience. I detail a class assignment in which students produce a social media project that imparts academic knowledge to a general audience. These have taken the form of short videos, websites, a documentary and even poems and songs. Drawing on a survey of the students, as well as a content analysis of the projects, I find that the project is successful in achieving several teaching goals, including knowledge retainment, critical thinking skills, making real world connections with class material, student empowerment, and improving communication skills.